Pengaruh Penambahan Gula Aren Terhadap Karakteristik Selai Labu Siam (Sechium edule) - Deniari, Komang Redita; Nocianitri, Komang Ayu; Suparthana, I Putu (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2025)
Jam is considered as semi-solid food made from fruit puree with added sugar and then it was cooked until thickened. Chayote has fairly high pectin content so that it has the potential to be used as jam. Palm sugar is a type of sugar which can be used as an alternative to cane sugar since it has a distinctive aroma and color; besides, it has a low glycemic index. The aims of this study were to determine the effect of adding palm sugar on the characteristics of chayote jam and to determine palm sugar concentration which can produce chayote jam with the best characteristics. This study used a completely randomized design with palm sugar concentration treatment which consisted of 6 levels, namely 30, 35, 40, 45, 50 and 55 percent. Each treatment was repeated 3 times in order to obtain 18 experimental units. Research data was analyzed by using Analysis of Variance (ANOVA) and if there was a significant effect (P<0.05) then it was continued with the Duncan Multiple Range Test. The result showed that palm sugar concentration had a significant effect (P<0.05) on water content, viscosity, total sugar, total dissolved solids, color, aroma, texture, taste, overall acceptace and sweetness of chayote jam. Palm sugar concentration of 55 percent produced chayote jam with the best characteristics with water content of 27.98 percent, viscosity of 29.47 Pa.s, acidity degree of 5.00, total sugar of 55.99 percent, total dissolved solids of 58.93 percent Brix, with sensory criteria of preferred color, aroma, texture, and overall acceptace with preferred sweetness. Keywords: jam, chayote, palm sugar, sugar concentration